Cholesterol-functionalised mesoporous silica nanoparticles for removal of naphthalene from water. Issue 4 (16th March 2023) - Beagan, Abeer M.
ABSTRACT: This work introduces the synthesis of mesoporous silica nanoparticles (MSNs) with high surface area and average pore size of ca. 4 nm. MSNs were modified with amine groups and then reacted with succinic anhydride. Cholesterol was attached to MSNs surface via an esterification reaction between hydroxyl and carboxylic groups in acidic media. Thereafter, the cholesterol-functionalised MSNs were used to remove naphthalene from the water with high removal efficiency, compared to unmodified surface. The fabricated nanoparticles were analysed with some physico-chemical techniques such as transmission electron microscopy (TEM), Fourier Transform Infrared (FTIR) spectroscopy and thermogravimetric analysis (TGA).